IgM antibody responses against Plasmodium antigens in neotropical primates in the Brazilian Atlantic Forest - Assis, Gabriela Maíra Pereira de; Alvarenga, Denise Anete Madureira de; Souza, Luisa Braga e; Sánchez-Arcila, Juan Camilo; Silva, Eduardo Fernandes e; Pina-Costa, Anielle de; Gonçalves, Gustavo Henrique Pereira; Souza, Júlio César de Junior; Nunes, Ana Julia Dutra; Pissinatti, Alcides; Moreira, Silvia Bahadian; Torres, Leticia de Menezes; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Zoonotic transmission is a challenge for the control and elimination of malaria. It has been recorded in the Atlantic Forest, outside the Amazon, the endemic region in Brazil. However, only very few studies have assessed the antibody response, especially of IgM antibodies, in Neotropical primates (NP). Therefore, in order to contribute to a better understanding of the immune response in different hosts, and facilitate the identification of potential reservoirs, here naturally-acquired IgM antibody responses against Plasmodium antigens were evaluated, for the first time, in NP from the Atlantic Forest. The study was carried out using 154 NP samples from three different areas of the Atlantic Forest. IgM antibodies against peptides of the circumsporozoite protein (CSP) from different Plasmodium species and different erythrocytic stage antigens were detected by ELISA. Fifty-nine percent of NP had IgM antibodies against at least one CSP peptide, and 87% against at least one Plasmodium vivax erythrocytic stage antigen. Levels of antibodies against PvAMA-1 were the highest compared to the other antigens. All families of NP showed IgM antibodies against CSP peptides, and, most strikingly, against erythrocytic stage antigens. Generalized linear models demonstrated that IgM positivity against PvCSP and PvAMA-1 was associated with PCR-detectable blood stage malaria infection and the host being free-living. Interestingly, animals with IgM against both PvCSP and PvAMA-1 were 4.7 times more likely to be PCR positive than animals which did not have IgM for these two antigens simultaneously. In conclusion, IgM antibodies against different Plasmodium spp. antigens are present in NP from the Atlantic Forest. High seroprevalence and antibody levels against blood stage antigens were observed, which had a significant association with molecular evidence of infection. IgM antibodies against CSP and AMA-1 may be used as a potential marker for the identification of NP infected with Plasmodium, which are reservoirs of malaria in the Brazilian Atlantic Forest.